Electrical Characteristics of Planar Pbthalocyanine Thin Films - Mohammed, K. A (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The   electrical     properties   of   thin   film    interdigital    metalÂphthalocyanine - metal devices have been studied with regard to purity and electrode material . Devices utilising phthalocyanines ( H2 Pc ,NiPc and CuPc) films with Au, Ag , Cu ' In and AI electrodes have been prepared with Pc layers fabricated  from  both as - supplied  Pc powder and entrainer - subeimed  material . The results indicate thatsublimed phthalocyanine with gold electrodes offers the best materialcombination with regard to linearity , reversibility and reproducibility. Measurements  of  current        temperature  characteristics  of phthalocyanines  indicate that the impurity of the film have a majorinfluence on conduction mechanism.